The hemostatic system. 1st Part - Doris Barcellona; Francesco Marongiu (Hygeia Press di Corridori Marinella, 2019)
The hemostatic system is a complex ancestral pathway physiologically dedicated to protect the individual from bleeding. It starts immediately after an endothelial injury. Platelets and blood coagulation act synergically to provide a strength clot able to stop bleeding. In healthy subjects, the hemostatic system is able to work to avoid an excess of fibrin formation and deposition within the blood vessels on the one hand but is ready to stop bleeding on the other. To reach this crucial objective, a fine regulation of its activity is required. In other words, all actions of the hemostatic system are under control to assure a perfect balance to maintain people distant from both Scylla (bleeding) and Charybdis (thrombosis). Fibrinolysis is a complementary defensive system essential to regulate fibrin deposition via its dissolution. It is, in turn, well controlled to avoid bleeding and thrombosis by a fine control of its inducers and inhibitors. The aim of this review is to provide a picture of global haemostasis for helping in understanding this complex topic.